Systematic Literature Review: Pengaruh Permainan Tradisional Terhadap Kelincahan Siswa Sekolah Dasar - Rachman, Fadlu; Prasetiyo, Andri; Rahmat, Ayi; Nuruhidin, Ahmad (Jurnal Porkes, 2025)
Traditional games contribute significantly to improving the agility of elementary school students. However, technological developments and lifestyle changes have led to a decline in physical activity among children. This study aims to systematically examine the impact of traditional games on the agility of elementary school students. The method used is a systematic literature review (SLR) by analyzing published research between 2019 and 2024 through Google Scholar, SINTA, and Publish or Perish. Of the 40 articles identified, 7 articles met the inclusion criteria. The results of the analysis showed that gobak sodor was able to increase agility by up to 67.5%, while bentengan increased agility by 9.7%. In addition, the games of lari balok, hadang, and sepak beleg were also proven to be effective in increasing students' agility. Compared to conventional exercises, traditional games are more interactive and can increase students' motivation to practice. In conclusion, traditional games can be applied as an effective strategy in physical education to develop the agility of elementary school students. Therefore, teachers, policymakers, and parents need to integrate traditional games into children's physical activities to support their motor development and fitness.